The city as a text and the participatory role of environmental graphics (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2019)
The promotion of the available resources and of the embedded fabric is fundamental both in central cities and in small towns, in the suburbs or in historic places. The fabric comes out of the combination between solids and voids, but also from the temporary works, exhibits, services and citizens that are part of it. The places make up the city are identified as real texts and not just as contexts. In so doing, the role of drawing and environmental graphics becomes more meaningful when it involves the communication area and it merges with the goods needed for everyday life. This paper focuses on the critical observation of some static or dynamic works, realised in different urban contexts: the covering of the construction sites’ fences, urban art, the conditions related to the events. The reflections help to develop the knowledge of the different forms of urban expressiveness and to highlight the increasing role of environmental graphics as a sign and a player of the on‒going social process: it promotes the user’s involvement that becomes more “citizen” and less customer than before.